Which frog’s legs do froggies eat? The use of DNA barcoding for identification of deep frozen frog legs (Dicroglossidae, Amphibia) commercialized in France - Ohler, Annemarie; Nicolas, Violaine (European Journal of Taxonomy, 2017)
Several millions frogs captured in the wild in Indonesia are sold for food yearly in French supermarkets, as deep frozen frog legs. They are commercialized as Rana macrodon, but up to 15 look-alike species might also be concerned by this trade. From December 2012 to May 2013, we bought 209 specimens of deep frozen frog legs, and identified them through a barcoding approach based on the 16S gene. Our results show that 206 out of the 209 specimens belong to Fejervarya cancrivora, two to Limnonectes macrodon and one to F. moodiei. Thus only 0.96 % of the frogs were correctly identified. Unless misclassification was intentional, it seems that Indonesian frog leg exporters are not able to discriminate between the species. The quasi absence of L. macrodon in our samples might be an indication of its rarity, confirming that its natural populations are declining rapidly, in agreement with its “vulnerable” status according to the IUCN Red List. Our results show that the genetic and morphological diversity of the frogs in trade is much higher than the genetic and morphological diversity measured so far by scientific studies. These results underline the need for large scale studies to assess the status of wild populations.